Finance-oriented directors and crisis management: Blissful ignorance in the hospitality industry?. (September 2017) - Iaquinto, Anthony L.; Jannicelle, Vivien; Macpherson, Wayne G.
Abstract: The primary purpose of this study was to examine the demographic characteristics of Boards of Directors in the hospitality industry, and how those characteristics can impact a firm's performance during a major crisis. More specifically, using the upper echelons perspective, this study examined the impact of finance-oriented directors, and directors who were outsiders, on a company's stock price during the great recession. Results using companies from the hospitality industry indicate that companies that had the highest percentage of finance-orientated directors tended to fall further and recover less quickly. Yet, in the aftermath of the crisis, companies that performed worse during the crisis tended to increase the percentage of finance-oriented directors. The authors of the study assert that extending the application of the blissful ignorance effect is a logical explanation for the behavior found in the results.